Pembiasaan Pembacaan Pali Wacana Paritta di Pusat Pendidikan Dan Latihan Sikkhadama Santibhumi - Iin Suwarni (Jurnal Pelita Dharma, 2018)
The problem examined in this study was the Habit of Pāli Wacana Paritta at the Sikkhadama Santibhumi Training Center in Tangerang. Beginning to hear the Pāli paritta discourse in several monasteries/cetiya there were differences caused by the local dialect. In fact, the difference in reciting the paritta in Pāli wacana is not a mistake as the dialect of each person cannot be forced. However, actually this can be attempted so that uniformity occurs in the context of the paritta discourse, because actually there is the same Pāli grammar. So the purpose of this study was to describe the habituation of the paritta discourse at the Sikkhadama Santibhumi Training Center in Tangerang.This research is a qualitative descriptive study. The subjects of this study were Sangha Bhikkhu, Romo/Ramani, administrators, SMB supervisors and Sikkhadama Pusdiklat Santibhumi people. The object in this study was the habituation of the discourse at the Sikkhadama Santibhumi Training Center in Tangerang. Data collection techniques by means of interviews, documentation and observation. Qualitative data analysis using the Miles and Huberman models. Through this research, the researcher described the phenomenon of the habituation of the paritta discourse at the Sikkhadama Santibhumi Training Center in Tangerang.The results of this study indicate that the process of habituation of the paritta discourse went smoothly with the guidance of the Sangha Bhikkhu. Even though the process is always given the procedure for reading. This is because the people who come from different Buddhist backgrounds. The determinants of the level of success in the implementation of the pitta of the paritta discourse include the guidance of the devotional service. With good worship leaders, the people will follow the parish discourse well. Masalah yang diteliti dalam penelitian ini  adalah pembiasaan Pāli Wacana Paritta di Pusat Pendidikan dan Latihan (Pusdiklat) Sikkhadama Santibhumi Tangerang. Berawal dari mendengar pembacaan Pāli wacana paritta di beberapa wihara/cetiya ternyata terdapat perbedaan yang disebabkan oleh dialek setempat. Sebenarnya perbedaan cara membaca Pāli wacana paritta bukan merupakan kesalahan karena memang dialek tidak dapat dipaksakan. Namun, sebenarnya hal tersebut dapat diupayakan agar terjadi keseragaman dalam Pāli wacana paritta, karena sesungguhnya terdapat tata bahasa Pāli yang sama. Tujuan penelitian ini mendeskripsikan pembiasaan pembacaan Pāli wacana paritta di Pusdiklat Sikkhadama Santibhumi Tangerang.Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah Bhikkhu Sangha, Romo/Ramani, pengurus, pembimbing Sekolah Minggu Buddha (SMB), dan umat Pusdiklat Sikkhadama Santibhumi. Objek penelitian ini adalah pembiasaan pembacaan Pāli wacana di Pusdiklat Sikkhadama Santibhumi Tangerang. Teknik pengumpulan data dengan cara wawancara, dokumentasi, dan observasi. Analisis data kualitatif menggunakan model Miles Hubberman. Melalui penelitian ini, peneliti mendeskripsikan fenomena pembiasaan pembacaan Pāli wacana paritta di Pusdiklat Sikkhadama Santibhumi Tangerang.Hasil penelitian ini menunjukkan bahwa proses pembiasaan pembacaan Pāli wacana paritta berjalan dengan lancar atas bimbingan Bhikkhu Sangha. Meskipun dalam prosesnya selalu diberikan arahan tata cara pembacaannya. Hal tersebut dikarenakan umat yang hadir dari latar belakang Agama Buddha yang berbeda. Penentu tingkat keberhasilan dalam pelaksanaan pembiasaan pembacaan Pāli wacana paritta di antaranya oleh pemandu puja bakti. Dengan pemimpin puja bakti yang baik maka umatnya akan mengikuti pembacaan Pāli wacana paritta dengan baik.